Improving Islamic Financial Reporting Transparency Through Aaoifi Standards: Building Trust and Investor Confidence in Russian Partnership Finance - Kharisova, Firdaus; Derzayeva, Guzel; Aletkin, Pavel (Journal of Sustainable Competitive Intelligence, 2025)
Purpose: The purpose of the study is to identify possible areas of using foreign experience in assessing annual reports of Islamic financial organizations for Russian partner financing organizations. Methodology/approach: Using general economic methods as comparison, contrast, analysis, synthesis, and systemic approaches, the authors examined annual reports of several Islamic financial organizations and highlighted applicable foreign practices. Originality/Relevance: The subject of the article is annual reports of Islamic financial organizations, the object of the study is foreign experience in assessing annual reports of Islamic financial organizations. Key findings: Based on the results of the study, it was found that Russian partner financing organizations can apply AAOIFI standards, establish Sharia supervisory boards, expand disclosure on products, services, ethics, and social programs, and use sukuk-based hedging. These measures support access to Islamic capital markets and attract Gulf investments. Theoretical/methodological contributions: The study offers methodological guidance for aligning Russian reporting with international Islamic finance practices, contributing to both theory and applied governance.